Sapotaceae endémicas del Perú - León, Blanca (2006)
The Sapotaceae are represented in Peru by 10 genera and 90 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all trees. Here we recognize eight endemic species in four genera. Pouteria is the genus with more endemic species. Endemic species are found in Very Humid Premontane Forests, Humid Lowland Amazonian Forests, Very Humid Montane Forests and Mesoandean regions, between 100 and 2500 m elevation. One endemic species has been recorded within Peru’s protected areas system.